IMMATERIAL CULTURAL ELEMENTS PATRIMONIAZATION AND LOCAL SUSTAINABLE DEVELOPMENT - Rosa, Alejandro Martínez-de la (Universidad Autónoma Indígena de México, 2018)
Tourism and heritage studies in Mexico are mainly focused on two major areas: specific ecological areas and historical edifications. However, in the last ten years they have proposed initiatives to consider the practices related to the state and federal levels immaterial. Until today there are seven elements in the UNESCO’s Representative List of Intangible Cultural Heritage belonging to Mexico. From conceptual review of the terms used to justify the safeguarding of intangible cultural heritage in international conventions of the past fifty years, it will reflect on the relationship between processed of patrimonialization and sustainable development projects, first from a general point of view about specific problems of application in Mexico for later review.